ETHNOKNOWLEDGE OF INDICATOR PLANTS IN LANDSCAPE OF FAXINALENSE SUBSYSTEM ‘PLANTING LANDS’, RIO AZUL - PR (PerCursos, 2021)
This article aims to understand the ethnoknowledge of the indicator plants in relation to landscape of the ‘planting lands’ of Faxinal Taquari dos Ribeiros, Rio Azul - PR. Methodologically the work began with the application a pilot test. Then, open, semi-structured and unstructured interviews were used. Subsequently, there was a guided tour (ethno-hiking) for collection of indicator species and their identification in the laboratory. Thus, it was possible to list 42 ethnospecies, 32 of which were related only to land quality and 10 directly correlated to land types (White, Black and Purple). The classification of spontaneous vegetation and its relationship with the lands reveals that the evaluative logic of productive potential of the landscape occurs in a synthetic way. In the landscape, therefore, there is an inextricable relationship between human groups and nature, in which the forms, contents and knowledge of this interaction are presented.
Keywords: Faxinal Taquari dos Ribeiros; landscape; ethnoknowledge; indicator plants; lands quality